A narrative review on diagnosis and treatment of ifosfamide-induced encephalopathy, the perspective of a EURACAN reference center for sarcomas - Torchia, A.; Vari, S.; Onesti, C. E.; Ceddia, S.; Maschio, M.; Maggi, G.; Riva, F.; Faltyn, W.; Russillo, M.; Ferraresi, V. (Frontiers in Pharmacology, 2025)
Ifosfamide (IFO) is a nitrogen derivative used at different doses, alone or in combination, in the treatment of various types of solid and hematologic cancers. It is a pro-drug activated by cytochrome P450 enzymatic system into ifosforamide mustard, the alkylating component that carries out the cytotoxic effect of the IFO. The most common toxicities of IFO are gastrointestinal, cutaneous, hematological, urological, and neurological. The neurotoxicity may occur in up to 30% of patients and can manifest with a wide spectrum of clinical presentations (lethargy, somnolence, confusion, hallucinations, irritability, excitement, disorientation, weakness, seizures, movement disorders, coma) and a variety of EEG abnormalities, and is known as IFO-induced encephalopathy (IIE). There is no definitive explanation of the mechanism underlying this phenomenon, even though metabolism of IFO, which leads to the formation of neurotoxic components, is probably at the basis of neurotoxicity according to many hypotheses. Consequently, the different factors involved in IFO metabolism (i.e., genetic polymorphism of CYP2B6, GSTM1, GSTP1, and GSTT1; concomitant administration of drugs that affect the cytochrome P450 enzyme system; drug formulation) could be responsible of IIE. IIE is usually reversible by interrupting the IFO infusion and starting intravenous hydration but in some cases further interventions are needed. The most used pharmacological treatment is methylene blue, whose efficacy both as a curative and a prophylactic treatment has been the object of many studies, with mixed results. Other interventions that showed efficacy are thiamine (tested also as a prophylactic drug), dexmedetomidine, and hemodialysis. Other pharmaceuticals have been tested in a preclinical setting showing some activity: trifluoperazine, morin, caffeic acid phenethyl ester (CAPE), and alpha lipoic acid (ALA). The aim of this review is to gather the current knowledge about the mechanisms underlying the IIE and the current therapeutic approach and the future perspectives.